Service Quality, Visitor Satisfaction And Behavioural Intentions Towards Public Museums In Malaysia - Lau , Pei Mey (2011)
Museum, as a niche product of Malaysia‟s cultural heritage tourism industry, is one of the sectors that could promote the growth of the tourism industry in the country. Given the increasing competitive phenomenon of the tourism industry, this study aimed to assess the visitors‟ perceptions of the service quality, the satisfaction levels, and the behavioural intentions towards public museums in Malaysia by applying the modified version of the SERVPERF model. This study was also set out to explore the relationships between the overall service quality, the overall visitors satisfaction and the behavioural intentions of visitors.